Independence in Activities of Daily Living Among Community-Dwelling Older Adults: A Cross-Sectional Study - Aniek Puspitosari; Ninik Nurhidayah (SENTRI: Jurnal Riset Ilmiah, 2025)
Older adults constitute a vulnerable population experiencing declines in physical, psychological, and social functioning, which may compromise their independence in performing activities of daily living (ADL). Maintaining ADL independence is essential for preserving quality of life, autonomy, and reducing dependency on family and long-term care services. Elderly associations serve as important community-based platforms that support social and psychological well-being; however, empirical evidence regarding ADL independence among their members remains limited. This study aimed to analyze the level of independence in activities of daily living among community-dwelling older adults. An analytical cross-sectional survey was conducted involving 101 elderly individuals residing in Kebakkalang RW VIII, Kemiri, Kebakkramat, Karanganyar. Independence in ADL was assessed using the Katz Index. The findings indicate that more than half of the respondents demonstrated independence in performing daily activities, suggesting a generally favorable functional status among elderly individuals engaged in community-based social groups. This level of independence reflects the potential role of social participation and community support in maintaining functional ability among older adults, particularly in early old age. These results provide important empirical evidence for healthcare providers, families, and community stakeholders to develop targeted preventive and promotive interventions aimed at sustaining and enhancing functional independence among older adults living in the community.